Bahasa dan Aksara dalam Penulisan Tafsir Al-Qur’an di Indonesia Era Awal Abad 20 M - Gusmian, Islah (Mutawatir : Jurnal Keilmuan Tafsir Hadith, 2015)
Language and script in the writing of Qura’nic tafsir in Indonesia is not only used for communication tools, but it is also being a part of social and cultural cognition. This article investigates the relational and diverse interest in the practical life of Qur’anic interpretation. The local practice of Javanese script (pegon) for example, is commonly used by the community of pesantren and it is widely read by its students (santri). The practice of Cacarakan is also vastly used in the local context that is relevant to the social tradition of palace (keraton) community. On the other hand, the usage of Pegon, Bugis and Cacarakan in the writing of Qur’anic interpretation has experienced various difficulties, primarily in the issue of transforming Arabic vocabularies that however the scriptural features is not really applicable to the local features of Nusantara scripts.